Writing and Publishing a Scientific Research Paper - López Leyva, Santos (2013)
This paper summarizes a didactic experience. It has been used in a research course taught in a Mexican university for the preparation of scientific papers.  It highlights the importance of scientific papers as dissemination channels for science and describes the steps for publishing in specialized journals. The concept and structure of scientific papers are explained. This study includes the analysis of the main sections in a scientific paper: introduction, methods, results, discussion, and conclusions, as well as the connecting sections: title, abstract, key words, acknowledgments, references, and annexes. It provides recommendations on writing these sections, preparing the manuscript, and the steps to accomplish in the publication process. In addition, based on interviews to six researchers, this paper points out limitations and provides recommendations on writing and publishing a scientific paper.